Three missing days ebook - Coble, Colleen (Pelican Harbor, 2021)
Police Chief Jane Hardy's teenage son has been accused of a horrific crime—and three days of Jane's memories have been stolen from her. In the gripping third installment of the Pelican Harbor series from USA TODAY bestselling author Colleen Coble, the truth is finally coming out. Chief of Police Jane Hardy plunges into the investigation of a house fire that claimed the life of a local woman as well as one of the firefighters. It's clear the woman was murdered. But why? The unraveling of Jane's personal life makes answers for the case even more difficult to find. Then Jane's fifteen-year-old son is accused of a terrible crime, and she has to decide if she can trust her ex, Reid, to help her prove Will's innocence—and if she can trust Reid with her heart. Three days of Jane's past are missing from her memory, and that's not all that's been stolen from her. As she struggles to find the murderer and clear her son's name, finding out what happened in those three days could change everything. It all started with one little lie . . . but the truth is finally coming out. "Coble's clear-cut prose makes it easy for the reader to follow the numerous scenarios and characters. This is just the ticket for readers of romantic suspense." —Publishers Weekly Readers love these novels because of the strong, relatable characters, the fast-paced suspense, the layers of family drama, and the themes of redemption. The Pelican Harbor Series is best read in order and includes One Little Lie, Two Reasons to Run, and Three Missing Days. Each novel contains discussion questions perfect for book clubs. Looking for more from these characters? Find cameo appearances from them in the Tupelo Grove Series from Colleen Coble and Rick Acker (What We Hide, Where Secrets Lie, and When Justice Comes).